Micro-DSC, rheological and NMR investigations of the gelation of gallic acid and xyloglucan - Hirun, Namon (2013)
A novel thermoreversible gelling system consisting of tamarind seed xyloglucan (TSX) and gallic acid (GA) was prepared and investigated. The thermal transition temperatures obtained from both micro-DSC and viscoelastic methods were consistent. The hysteresis was observed for the GA–TSX gelling system. The hydrogen bonding interactions between GA and TSX were detected using 13C nuclear magnetic resonance analyses. The carboxylic acid and the hydroxyl group at the para position of GA are the principal groups that interact with TSX. A low temperature induced intermolecular aggregation of TSX via hydrogen bonds between GA and TSX, leading to the formation of a gel network. The thermal stability of the GA–TSX gel increased with increasing the GA concentration. The viscoelastic behavior of the GA–TSX mixtures depended on the concentration of GA. For the mixture of GA and 1% (w/v) TSX, the critical gel concentration of GA was 0.69% (w/v) at physiological temperature (37 °C) and the sol–gel transition was well described by the scaling law. Moreover, the dried GA–TSX gels exhibited various morphologies that reflected the dependence of the arrangement of the TSX chains on the GA concentration.